What’s in a Name? The Influence of Persuasive Communication on Florida Consumers’ Attitude toward Genetically Modified Food - Taylor K. Ruth; Joy N. Rumble (Journal of Applied Communications, 2017)
Consumer acceptance of new food technology, like genetically modified food, is essential for the product’s success. Consumers have been skeptical toward the technology of genetically modified food due to lack of knowledge by the public, negative portrayal of the technology by the media, and a lack of communication about the technology from those who develop and use it. This research was guided by the Elaboration Likelihood Model to investigate the influence of persuasive communication on Florida consumers’ attitude toward genetically modified food. Consumers typically use the peripheral route to assess food information, therefore a message source (peripheral cue) was manipulated to examine its effect on attitude. An experimental design administered through an online survey was used to collect data (n = 515). Respondents reported that they agreed they were knowledgeable about genetically modified food, but they were unsure about associated risks. Respondents neither agreed nor disagreed that the four sources were credible, and there were no differences in credibility. Additionally, there were no differences in their attitude toward genetically modified food associated with the source. The results showed that the source did not predict attitude, but source credibility, risk perception, and some demographic characteristics did. Prior knowledge was not a predictor of attitude, and the respondents likely used the peripheral route to assess the message. Agricultural communicators should target communication for specific audiences and deliver value-driven messages rather than trying to increase consumer knowledge alone. Future research should explore different peripheral cues and their effects on attitude formation.
Keywords: Credibility; Elaboration Likelihood Model; Genetically Modified Food; Message Source; Risk Perception